From Market-Places to a Market Economy: The Transformation of Rural Massachusetts, 1750-1850 - Winifred Barr Rothenberg (Chicago: The University of Chicago Press, 1992)
"One of the most important books ever written about the economic history of early America." - Gordon S.Wood, Brown University.
(NP(B/13590s
+Photos
Keywords: history -- markets -- growth -- economy